Politics or Technocracy – What Next for Global Health?: Comment on "Navigating Between Stealth Advocacy and Unconscious Dogmatism: The Challenge of Researching the Norms, Politics and Power of Global Health" - Kickbusch, Ilona (Int J Health Policy Manag, 2015)
Politics play a central part in determining health and development outcomes as Gorik Ooms highlights in his recent commentary. As health becomes more global and more politicized the need grows to better understand the inherently political processes at all levels of governance, such as ideological positions, ideas, value judgments, and power. I agree that global health research should strengthen its contribution to generating such knowledge by drawing more on political science, such research is gaining ground. Even more important is – as Ooms indicates – that global health scholars better understand their own role in the political process. It is time to acknowledge that expert-based technocratic approaches are no less political. We will need to reflect and analyse the role of experts in global health governance to a greater extent and in that context explore the links between politics, expertise and democracy.